Role of Doc2β in regulated exocytosis of large dense-core vesicles in bovine adrenal chromaffin cells - Tapechum, Sompol (The University of Edinburgh, 2003)
Doc2ß is a member of the double C2-domain (Doc2) protein family, a novel family of proteins having two C2 domains. Doc2ß is highly enriched in brain where it is associated with synaptic vesicles. However, Doc2ß is also expressed in nonneuronal tissues. Like its brain-specific counterpart Doc2a, Doc2ß interacts with Ca²⁺, phospholipids, Muncl3 and Muncl8, all of which are important elements for regulated exocytosis. While the significant role of Doc2a in regulated exocytosis was confirmed in PC 12 cells, the role of Doc2p in regulated exocytosis is still unresolved. Given the high homology, the complementary distribution in brain, the similarities in Ca²⁺-dependent phospholipid binding and interaction with other synaptic proteins between Doc2α and Doc2ß, it is hypothesised that Doc2ß performs a similar function in regulated exocytosis as Doc2α. The aim of this thesis is to study the possible roles of Doc2ß in regulated exocytosis and to elucidate the mechanisms of action.

The adrenal chromaffin cell has been a popular model cell for the study of exocytosis. This cell contains catecholamine packaged in large dense-core vesicles (LDCVs) that undergo Ca²⁺-dependent exocytosis based on molecular machinery similar to that of synaptic transmission. Heterologous protein expression was achieved by using a Semliki Forest Virus (SFV) vector system, yielding high efficiency expression and minimal interference of membrane trafficking. Secretion was studied in both cell-population and single-cell levels. At the cell-population level, secretion of catecholamine was detected by using spectrofluorimetry. High resolution monitoring of secretion was achieved by using membrane capacitance measurements and electrochemical detection of catecholamine.

Expression of Doc2ß fusion with green fluorescent protein (Doc2ß-EGFP) in bovine adrenal chromaffin cell showed both cytoplasmic and nuclear localisation. Punctate cytoplasmic fluorescence was identified in some cells which indicated the association with some intracytoplasmic compartments. Deletion of the amino terminal of Doc2ß (C2AB-EGFP) did not change the fluorescence distribution pattern. The expression of Doc2ß did not affect calcium currents and intracellular calcium level. Secretion induced by 50 mM KC1 depolarisation in intact cells or 1 μM free Ca²⁺ in ß-escin-permeabilised cells was not different among cells expressing green fluorescent protein, cells expressing wild-type Doc2ß and cells expressing Nterminal deletion of Doc2ß (C2AB). Secretion induced by whole-cell dialysis with solution containing 10 pM free calcium was also not different among those groups. The fusion-competent vesicle pool was not significantly changed by the expression of Doc2ß or C2AB. Application of phorbol ester similarly increased the fusioncompetent vesicle pool and catecholamine secretion in all cell groups. The results from this study indicate that Doc2ß is not essential for regulated exocytosis of LCDVs in bovine adrenal chromaffin cells.